Analisis Kadar Serat dan Protein Total Sereal Berbasis Tepung Ampas Kelapa dan Ikan Cakalang (Katsuwonus pelamis): Analysis of Fiber Content and Total Protein of Cereal Based on Coconut Pulp and Skipjack Tuna (Katsuwonus pelamis) Flour - Nanda Novita; Nurhaeni; Prismawiryanti; Abd. Rahman Razak (KOVALEN: Jurnal Riset Kimia, 2020)
Research on the analysis of fiber and protein on cereal based on coconut pulp and skipjack tuna (Katsuwonus pelamis) flour has been carried out. The purpose of this study was to determine the ratio of coconut pulp flour and skipjack tuna flour which produced the highest fiber content and protein content in cereal processed products and to know the preference level of panelists for cereal processed products. The ratio of coconut pulp and skipjack tuna flour used in this study, namely 25:75, 50:50, 75:25 (w/w), and without the addition of coconut pulp flour and skipjack tuna flour. The results showed that cereal with the highest fiber content was obtained at a ratio of 75:25 i.e. 10.52% and the lowest fiber content was obtained at the cereal without the addition of coconut pulp flour and skipjack tuna flour i.e. 1.19%, whereas the highest protein content of cereal was obtained at a ratio of 25:75 i.e. 26.02% and the lowest protein content was obtained at the cereal without the addition of coconut pulp flour and skipjack tuna flour i.e. 9.17%. The highest preference level (5.57) of the panelists for the cereal flour of coconut pulp and skipjack tuna flour is the 75:25 ratio. Keywords: Skipjack tuna flour, coconut pulp flour, cereal, fiber, protein